2017
DOI: 10.3390/jcdd4030008
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Species Comparison of Cardiac Troponin T and Dystrophin: Unravelling the DNA behind Dilated Cardiomyopathy

Abstract: Animals have frequently been used as models for human disorders and mutations. Following advances in genetic testing and treatment options, and the decreasing cost of these technologies in the clinic, mutations in both companion and commercial animals are now being investigated. A recent review highlighted the genes associated with both human and non-human dilated cardiomyopathy. Cardiac troponin T and dystrophin were observed to be associated with both human and turkey (troponin T) and canine (dystrophin) dil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 149 publications
0
9
0
Order By: Relevance
“…Exon 8 skipping in affected individuals has been a suggested link in cardiac troponin T and it has also been indicated that wild turkeys have the similarly low molecular weight as exon 8 is spliced out [87]. This is also notable as humans carrying specific mutations in troponin T are also affected by cardiomyopathies [88]. Over 90 mutations have been described in the troponins in humans to date which result in heart disorders including hypertrophic, dilated and restrictive cardiomyopathy in addition to left ventricular non-compaction.…”
Section: Cardiomyopathiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Exon 8 skipping in affected individuals has been a suggested link in cardiac troponin T and it has also been indicated that wild turkeys have the similarly low molecular weight as exon 8 is spliced out [87]. This is also notable as humans carrying specific mutations in troponin T are also affected by cardiomyopathies [88]. Over 90 mutations have been described in the troponins in humans to date which result in heart disorders including hypertrophic, dilated and restrictive cardiomyopathy in addition to left ventricular non-compaction.…”
Section: Cardiomyopathiesmentioning
confidence: 99%
“…Over 90 mutations have been described in the troponins in humans to date which result in heart disorders including hypertrophic, dilated and restrictive cardiomyopathy in addition to left ventricular non-compaction. It has also been highlighted that despite variable regions of troponin, there are some areas which are highly conserved between species including most mammals, turkeys and chickens [88]. The areas containing the most causative mutations in humans are the T1 terminal and the C-terminal and cardiac troponin T, therefore these regions make excellent candidates for future studies, not only in turkeys but in other birds too.…”
Section: Cardiomyopathiesmentioning
confidence: 99%
“…It is one of several different types of "cardiomyopathy, " heart disorders that are seen in humans and animals. Common types of cardiomyopathy are called: (1) hypertrophy; (2) dilated; and (3) restrictive [1].…”
Section: How Do Hearts Get Broken?mentioning
confidence: 99%
“…Given the rapid development of and stress exposure in broilers and the sudden death syndrome associated with cardiovascular diseases due to lubrication in internal organs, broilers breeding facilities are associated with high mortality. Studies have shown that the mortality rate is doubled in birds fed high-protein diets (Breeding et al, 1994;England et al, 2017). Cardiomyopathies are diseases of the heart muscle that result from heart failure and cause cardiac dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiomyopathies are associated with decreased diastolic volume especially in the ventricles, a dilated atrium, limited ventricular filling and rarely, ventricular myocardial fibrosis. In this case, fat accumulation is caused by the prevention of electrical conduction and arrhythmias (Maron et al, 2006;Wieczorek et al, 2008;Wexler et al, 2009;England et al, 2017).…”
Section: Introductionmentioning
confidence: 99%